EFEKTIFITAS SISTEM AKUNTANSI DALAM LAPORAN KEUANGAN PENGELOLAAN DANA DESA (Studi Kasus Pada Kelurahan Desa Karangdowo) - Khorisatul Amanah; Rohmad Abidin (UIN K.H. Abdurrahman Wahid Pekalongan, 2023)
This study aims to identify problems experienced by villages related to managing village funds and to understand more deeply about managing village funds using a computerized system, village fund reporting will be able to be done quickly and the output of financial reports will also be more reliable than manual reporting. The research method used is qualitative in a descriptive approach using observation techniques, interviews and data collection and documentation used for research results. And the sampel in this study was to find and collect data with an interview process, namely interviewing the secretary and treasurer in the village of karangdkowo village. In addition to providing information for the company so that it can improve the existing system in accordance with a good internal control system. In this study found the main problem that needs to be analyzed in the management of village funds, namely that there are still inadequate sources of network power and PLN which cause various kinds of obstacles in the process of managing village finances and also human resources which are still lacking and lagging behind cities or regencies. Village Accounting is a record of transaction processes that occur in the village. Evidenced by notes, then recording and financial reporting is carried out so that it will produce information in the form of financial reports that are used by several parties related to the village.